Old Lovegood girls - Godwin, Gail (New York : Bloomsbury Publishing, 2020)
A powerful friendship between talented writers -- two college friends who have formed a bond that takes them through decades of a fast-changing world, finding and losing and finding again the one friendship that defines them.
Keywords: Friendship -- Fiction; Authors -- Fiction; Schools -- Fiction; Women -- Fiction; Historical fiction; Domestic fiction